THE ACADEMIC-SCIENTIFIC PRODUCTION POST-GRADUATION PROGRAM IN EDUCATION OF UNESP/MARILIA-SP AND THE NATIONAL PUBLIC POLICY OF SPECIAL EDUCATION IN BRAZIL: HISTORICAL ASPECTS - Rosa Santana, Maria Silvia; Castro, Rosane Michelli de [UNESP]; Lima, Elieuza Aparecida de [UNESP] (Unesp-faculdade Ciencias & Letras, 2018)
This article presents results of our reflections carried out with the groups of studies and research that we integrate, focusing on the general objective of systematizing and analyzing theses and dissertations concluded between 2005 and 2008, in the line of research Special Education in Brazil, Program of Post-Graduation in Education of the FFC-Unesp /Martha. Such reflections were carried out considering that the changes, public policies aimed at the various social areas, as well as education are or should be boosted also by the results of academic-scientific research. In this sense, and after the investigations carried out, we conclude that the analyzed theses and dissertations were capable of pointing out and legitimizing, by the existent or the no, aspects of the struggles that were fought in Special Education in Brazil in an inclusive perspective, which culminated in the National Policy of Special Education and our country.
Keywords: Education; History of education; Special education; Academic-scientific production; National Policy on Special Education in Brazil